Selected traumatic factors and their impact on ill newborns in hospital conditions – part II. Pain and touch - Cepuch, Grażyna; Kruszecka-Krówka, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2019)
During hospitalisation an ill or prematurely born neonate is exposed to multiple environmental factors, including traumatic stimuli, such as overly frequent and intense touch, and severe pain related to caring, nursing, rehabilitation, and diagnostic-therapeutic activities. The exposure to traumatic touch and pain-generating activities can lead to serious, irreversible changes in the child’s development. It is also necessary to sensitise members of the medical team to the need of reducing a number of activities that are sources of stressful touch and pain. Care of the newborn should include regular pain assessment, the evaluation of procedural pain, and effective analgesic treatment using pharmacological and non-pharmacological methods.